Effectiveness and Side Effects of Natural and Modern Contraceptives in Multiparous Indonesian Families: Systematic Review - Shalvira Purnama; Saufa Ayudia Pratiwi; Vincent Christopher Pakendek; Tsabitha Ramadhani; Muhammad Awaludin Rachman; Arroyyani Shofiatun Nisa'; Arifin Ilham Syafa'at; Theodorus Sebastian De Rozari; Maryam Shabrina; Syarifah Saniinah Yasmine; Khairunnida Rahma (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Family planning enables couples to regulate childbirth and improve reproductive health. This systematic literature review compares the effectiveness and side effects of natural and modern contraceptive methods among multiparous families in Indonesia. The review followed the PRISMA guidelines. Literature searches were conducted through ScienceDirect, PubMed, and Google Scholar using the keywords